TRANSFORMASI DAN REINTERPRETASI PINTU GEBYOK JAWA DALAM DESAIN INTERIOR ETNIK KONTEMPORER DI BALI - Reandini Syu'ara Dewi; Ni Made Emmi Nutrisia Dewi; Ni Putu Eka Trisnasari Subrata (Waca Cipta Ruang, 2026)
This study aims to analyze the transformation and reinterpretation of the Javanese *gebyok* door in contemporary ethnic interior design in Bali as part of the material culture adaptation phenomenon. The *gebyok* is understood as a carved wooden partition element that embodies symbolic, cosmological, and social values in traditional Javanese architecture. This research employs a qualitative-descriptive approach using a literature-based method through the analysis and synthesis of relevant scientific sources published within the last ten years. The results indicate a transformation of function from a sacred structural element into a decorative element emphasizing aesthetic value in contemporary spaces, along with a reinterpretation of symbolic meaning from spiritual and cosmological values into representations of visual identity, prestige, and social differentiation. Furthermore, the findings reveal an integration of Javanese visual characteristics, which are structured and symmetrical, with the dynamic and contextual aesthetics of Balinese design, resulting in hybrid design forms.The implications suggest that the transformation of the *gebyok* not only contributes to innovation in interior design but also presents challenges in preserving cultural values, thus requiring a contextual design approach to maintain a balance between visual expression and cultural meaning.